Melanoma of anal canal - Gujar, Ajay; Pednekar, Jayant; Khan, Nida; Tiwary, Anurag; Chheda, Karna (International Surgery Journal, 2020)
Melanomas are primarily tumours of the skin, but rarely occur at other sites like retina and anal canal. Anorectal melanoma is an uncommon condition associated with a very poor prognosis. The patient usually presents with per rectal bleed or mass. These are often misdiagnosed on presentation. Diagnosis is confirmed by biopsy. Treatment is abdominoperineal resection or wide local excision if tumour free margins can be obtained. We present a case of a 60 years old female who presented to the outpatient department with per rectal mass and bleed since 4 to 5 months and was diagnosed with melanoma anal canal on biopsy. CT scan abdomen and pelvis was done. Patient underwent abdominoperineal resection as wide local excision with sphincter saving was not possible due to the location and extent of tumour as seen on CT scan. Patient had an uneventful recovery after the procedure.